Development and optimisation of a qPCR assay for the enumeration of Cryptophlebia leucotreta granulovirus (CrleGV) used for commercial applications - Mela, Thuthula (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
The citrus industry contributes significantly to the South African agricultural sector. Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) is highly important to the South African citrus industry as it is classified as a phytosanitary pest by most international markets. Thaumatotibia leucotreta has caused an estimated annual loss of up to R100 million to the industry. In order to control T. leucotreta in South Africa, an integrated pest management (IPM) programme has been used. One of the components of this programme is Cryptophlebia leucotreta granulovirus (CrleGV), which has been formulated to a registered biopesticide namely Cryptogran and has been successfully applied in the field for over 15 years. To use CrleGV as biopesticides, quantification of the viral particles is required to perform bioassays for field trials and formulation, among other applications. Darkfield microscopy is a traditional method used for the quantification of CrleGV; however, the method is characterised as being subjective, tedious, labour intensive, and time-consuming. This study aims to develop and optimise a qPCR technique to accurately quantify CrleGV-SA OBs using plasmid DNA for downstream applications. Firstly, lef-8, lef-9, and granulin conserved genes from CrleGV-SA and CrleGV-CV3 genome sequences were analysed by performing multiple alignments to evaluate the degree of identity between these genes. This was done to design two sets of oligonucleotides (internal and external) from regions with the highest identity. Subsequently, in silico testing was done to evaluate the designed oligonucleotides to determine whether they specifically bind to the selected target regions. Secondly, three sets of DNA plasmids (pJET1.2-Gran, pJET1.2-lef-9, and pJET1.2-lef-8) were constructed, each containing a target region for either granulin, lef-9, and lef-8 genes for use as standards in a downstream qPCR assay. This was achieved by first extracting gDNA from CrleGV-SA OBs and using the gDNA as a template to PCR amplify the target regions of the selected gene regions with the designed oligonucleotides. Subsequently, the PCR amplified regions were then directly ligated into the pJET1.2/blunt vector, and the plasmids were confirmed by colony PCR, restriction enzyme digestion, and Sanger sequencing. Thirdly, two different methods of CrleGV-SA gDNA extraction were compared to determine which method has the best yields in terms of concentration. The extraction methods compared were the Quick-DNA Miniprep Plus kit according to manufacturer's instructions (Method 1a), pre-treatment with Na2CO3 prior to using the Quick-DNA Miniprep Plus kit (Method 1b), pre- treatment with Na2CO3, and neutralisation with Tris-HCl prior to gDNA extraction using the Quick-DNA Miniprep Plus kit (Method 1c) and the CTAB method (Method 2). The gDNA concentration and purity for all samples were determined using a Nanodrop spectrophotometer. Method 1c (Na2CO3 and Tris-HCl pre-treated plus Quick-DNA Miniprep Plus kit) was the most efficient at extracting genomic DNA compared with the other methods, resulting in the highest DNA concentration in short processing time. Fourthly, plasmid standards were evaluated for use in the qPCR assay. This was done as it was important to consider the efficacy of the oligonucleotides; including the ability of the oligonucleotides to anneal to the appropriate segment of DNA without extensive formation of oligonucleotides dimers, non-specific annealing, or formation of secondary structure. In addition, it was done to ensure that highly accurate standard curves were generated. The standard curves were to be utilised in the downstream qPCR assay to determine the quantity of test samples by interpolation, reading from the values within the standard curve. Lastly, darkfield microscopy and qPCR methods of enumeration were compared to verify their accuracy and determine the most consistent and comparable method. This was achieved by quantifying the purified, crude-purified, and viral formulated CrleGV-SA suspensions using these methods. Subsequently, a statistical analysis was conducted to compare the results produced by the two enumeration methods. The obtained results showed that the granulin, lef- 8 and lef-9 qPCR values did not significantly differ from the darkfield microscopy results. The findings of this study revealed that the two assays, lef-8 qPCR and lef-9 qPCR, were more robust, sensitive, and efficient for the quantification of CrleGV-SA. Thus, this study has successfully developed a qPCR assay that is comparable with the traditional darkfield microscopy counting technique. This is the first study to use the qPCR technique to enumerate CrleGV-SA using plasmid standards. The developed qPCR assay is reliable, rapid, and cost- effective and has a great potential to be used as an alternative method to darkfield microscopy in the laboratory and commercial settings.
Keywords: Cryptophlebia leucotreta granulovirus; Cryptophlebia leucotreta; Late expression factor 8 (LEF-8); Late expression factor 9; Dark field microscopy; Genomic DNA; Polymerase chain reaction; Plasmids